Interoperability in The Indonesian Air Force Zero ... | Samsul Rizal and Safril Hidayat | 103 INTEROPERABILITY IN THE INDONESIAN AIR FORCE ZERO ACCIDENT POLICY - Rizal, Samsul; Hidayat, Safril (Jurnal Pertahanan dan Bela Negara, 2020)
The Zero Accident Policy is a priority of the Indonesian Air Force to reduce accidents and incidents in the aircraft operations of the Indonesian Air Force. Implementation of the policy can reduce the number of accidents and incidents that can cause casualties and Air Force Weapon System. However, the policy implementation is still done manually so that interoperability cannot be realized in implementing the policy. Using the interoperability business process approach, an analysis of the implementation of the Zero Accident Policy is carried out. This study uses a qualitative research design with primary data sources through purposive sampling. The results showed that the implementation of the policy using the interoperability system in the Zero Accident Policy had not been carried out by the Air Force sub organizations. This study recommends the use of application in order to realize the interoperability in the implementation of Zero Accident Policy. Keywords: policy, interoperability, zero accident.